Investigation on thermally-induced optical nonlinearity of alcohols. (June 2018) - Zhang, Qian; Cheng, Xuemei; He, Bo; Ren, Zhaoyu; Zhang, Ying; Chen, Haowei; Bai, Jintao
Highlights: Thermally-induced optical nonlinearity of alcohols is investigated. Nonlinear refractive index coefficient n 2 of ethanol is determined. Diffraction pattern is related to power, concentration and position of sample. Abstract: In this work, we studied the thermally-induced optical nonlinearity of alcohols by analyzing the far-filed diffraction rings patterns, which are generated when the alcohols are illuminated by a laser beam resonant to their overtones. We deduced the nonlinear refractive index coefficient n 2 generated by thermal nonlinear optical effect to be - ( 20.53 ± 00.03 ) × 10 - 8 cm 2 / W, which is much higher than that of Kerr effect ( 7.7 × 10 - 16 cm 2 / W ). The results also demonstrated that the thermally-induced optical nonlinearity increased with the laser power and sample concentration increasing. The notable nonlinearity suggests that thermal effect has potentials in many applications such as optical spatial modulation, and trapping and guiding of atoms.